Hubungan Pengetahuan dan Sikap Remaja Puteri Terhadap Pencegahan Anemia Di SMPN 19 Muaro Jambi - Nurmala; Rahmah; Rosa Riya; Silvia Mariana (STIKes Budi Mulia Sriwijaya, 2024)
The prevalence of anemia in Indonesia is 26.50% among adolescent girls. Anemia poses ahigher risk for adolescent girls compared to adolescent boys. The impact of anemia on adolescent girls will have negative consequences if they become pregnant during their teenage years or even as adults, which can lead to the birth of low birth weight babies, illness, and even death for both mother and child. Anemia also has negative effects on the physical and cognitive development of adolescents. The purpose is to determine the relationship between knowledge and attitudes of female adolescents towards the prevention of anemia at State Junior High School 19 Muaro Jambi. The research methode used is analytical survey research with a cross sectional approach. The population in this study consists of all frmale students at State Junior High School 19 Muaro Jambi, totaling 46 individuals. The sampling technique used is total sampling. Analyze the data using the chi-square test. The research results indicate that the majority of respondents have sufficient knowledge, with 21 respondents (45.7%), while most respondents have a negative attitude, totaling 24 respondents (52.5%). The bivariate data analysis revealed a relationship between knowledge (p=0.001) and attitude (p=0.000) regarding the prevention of anemia at State Junior High School 19 Muaro Jambi. There is a relationship between the knowledge and attitudes of adolescent girls towards the prevention of anemia at State Junior High School 19 Muaro Jambi.